Uptake of community pharmacist prescribing over a three-year period - Amy Grant; Shanna Trenaman; Samuel Stewart; Lihui Liu; Judith Fisher; Elizabeth Jeffers; Rebecca Lawrence; Andrea Murphy; Ingrid Sketris; Lisa Woodill; Jennifer E. Isenor (Elsevier, 2023)
Objectives: Pharmacists in Nova Scotia have had legislated authority to prescribe since 2011. This study aimed to describe the prescribing activities of pharmacists and the characteristics of patients who used pharmacist prescribing services. Methods: Using provincial health administrative databases we identified all community pharmacists who prescribed during the study period (October 2016 to March 2020) and correspondingly patients who had medications prescribed by a pharmacist during this period. Differences in, and predictors of the quantity of pharmacist prescribing over three fiscal years (April 2017 to March 2020) were described. Pharmacist prescribing activity was compared across the fiscal years of the study period with One-way Analysis of Variance. Negative binomial regression examined patient factors associated with use of pharmacist prescribing services. Analysis was carried out using SAS ENTERPRISE GUIDE v.8.2 (SAS Institute Cary, NC, USA). Key findings: A total of 1182 pharmacist prescribers were identified, who on average prescribed 24.6, 26.3, and 32.5 (p < 0.001) times per month in fiscal years 2018, 2019, 2020, respectively. The patient cohort contained 372,203 Nova Scotians over the 3-year period. For approved common and minor ailment prescribing in Nova Scotia, gastroesophageal reflux disease, vaccines (non-travel), contraceptive management, herpes zoster treatment, and allergic rhinitis had the highest number of prescriptions over the study period. Patient factors most strongly related to receiving more prescribing services by a pharmacist included receiving income assistance without copay (Incidence rate ratio (IRR) = 1.70), having >2 comorbidities (IRR = 1.51), male sex (IRR = 1.03), and greater age (IRR = 1.01). Those from an urban area (IRR = 0.92) or having a higher income (IRR = 0.95) received fewer pharmacist prescribing services (all p < 0.0001). Conclusions: Pharmacist prescribing increased over the 3-year period. Patients who were older and those with multiple comorbidities used pharmacist prescribing services most often. Prescribing activities represent an increasingly utilized role for pharmacists in primary care.